Hubungan Pengetahuan dan Sikap Masyarakat terhadap Pengelolaan Sampah di Desa Kujau Kecamatan Betayau Kabupaten Tana Tidung - Warni Warni; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2022)
This study is an expost-facto study that aims to examine whether there is a relationship between knowledge and attitudes on public waste management in Kujau Village of Betayau subdistrict in Tana Tidung district. The independent variables in this study are knowledge and attitudes, while the dependent variable is waste management. The population of the study were all heads of families in Kujau Village of Betayau subdistrict in Tana Tidung district, while the sample was 40 people obtained by employing Accidental Sampling Technique and the correct number of samples was above thirty and below five hundred. Data collection techniques employed questionnaires and interviews. The data analysis technique employed descriptive analysis and inferential analysis. Based on the results of inferential data analysis, it is discovered that there is a positive and significant relationship between knowledge and waste management at strong relationship level. The attitudes on waste have a positive and significant relationship on waste management at a very strong relationship level. There is a positive and significant relationship between knowledge and attitudes on public waste management which is in a very strong relationship.